Recognition and precarity of life arrangement: towards an enlarged understanding of precarious working and living conditions. Issue 2 (4th May 2019) - Motakef, Mona
ABSTRACT: Precarity and precarious work are widely debated concepts, though a lack of clarity remains about its definition, dimensions and application. Recognition appears to be an illuminating concept for a deeper understanding of work and employment in times of precarity and its further effects, but has yet to be considered. The article aims to develop a multifaceted understanding of precarity for empirical research. Hence, precarity of life arrangement is introduced as a heuristic, though it is developed further on the grounds of theories of recognition. The conceptual enlargement of precarity of life arrangement, further developed by theories of recognition, is the outcome of the article. To demonstrate the concept`s potential, of the spectrum of the empirical material of the study, the case of a couple in precarious working and living conditions is presented. Income and employment are important dimensions within the concept but are embedded in the life arrangement and hence intertwined with rights, love, participation, care, health and housing. The enlarged perspective developed in the articles stresses not only how precarity cumulates in life arrangement, but also gives insights into how precarity is mitigated and strengthened within the reciprocal relations of life dimensions and due to recognition (deficits).